2008
DOI: 10.1111/j.1365-2885.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and safety of zonisamide after intravenous and oral single dose and oral multiple dosing in normal hound dogs

Abstract: The purpose of this study was to determine an oral dosing regimen of zonisamide in healthy dogs such that therapeutic concentrations would be safely reached and maintained at steady-state. Adult hound dogs (n = 8) received a single IV (6.9) and an oral (PO) dose (10.3 mg/kg) using a randomized cross-over design. Zonisamide was then administered at 10.3 mg/kg PO every 12 h for 8 weeks. Zonisamide was quantitated in blood compartments or urine by HPLC and data were subjected to noncompartmental pharmacokinetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…Although ZNS is not FDA approved for use in dogs, it is now widely used as an anticonvulsant in this species . Limited information is available regarding safety, but small studies have suggested that routine clinical laboratory tests are unchanged with prolonged use, although serum thyroxine concentrations can be suppressed and mild hepatic changes might occur with sustained high doses (75mg/kg/day; approximately 5 times standard therapeutic doses) …”
mentioning
confidence: 99%
“…Although ZNS is not FDA approved for use in dogs, it is now widely used as an anticonvulsant in this species . Limited information is available regarding safety, but small studies have suggested that routine clinical laboratory tests are unchanged with prolonged use, although serum thyroxine concentrations can be suppressed and mild hepatic changes might occur with sustained high doses (75mg/kg/day; approximately 5 times standard therapeutic doses) …”
mentioning
confidence: 99%
“…In a pharmacokinetic study of healthy dogs given zonisamide at 10.3 mg/kg PO q12h for 8 weeks, mean serum total T4 concentration decreased below the normal reference range but mean free serum T4 and TSH concentrations were within the reference range after 6 months of treatment. Increases in serum ALP activity and serum calcium concentration and decreases in serum total protein and albumin concentrations were reported compared to baseline but remained within reference range 61. A small but statistically significant decrease in serum albumin concentration and an increase in ALP activity have been reported in research dogs given zonisamide at a dosage of 75 mg/kg/day for 52 weeks 98.…”
Section: What Are the Risks Of Treatment?mentioning
confidence: 80%
“…Metabolic tolerance is present when progressive dose increases without concurrent parallel increase in serum drug concentration occurs, most likely because of other drugs that are p450 enzyme inducers or genetic variations. Conversely, phenobarbital will increase clearance of several other AEDs, including levetiracetam,59, 60 zonisamide61 and clorazepate 62…”
Section: How Should Monitoring Be Performed?mentioning
confidence: 99%
“…Thus, knowledge of how long it takes to achieve a steady‐state plasma concentration and whether or not there is dose‐dependency is necessary to determine an optimal dosage regimen for zonisamide. There is one previous study concerning the pharmacokinetics after single and multiple administrations of zonisamide in dogs (Boothe & Perkins, 2008). However, dose‐dependency and time to achieve a steady state at a range of clinical doses of zonisamide are still unclear.…”
Section: Trough Concentrations Of Zonisamide In Plasma Whole Bloodmentioning
confidence: 99%